Assessment of the degree of adherence of medical laboratories to KDIGO 2012 guideline for evaluation and management of CKD in Czechia and Slovakia - Tomáš, Šálek; Bedřich, Friedecký; Josef, Kratochvíla; Květa, Pelinková; Marek, Budina (Biochemia medica, 2019)
Introduction: The aim of the study is to assess the degree of adherence of medical laboratories to Kidney Disease Improving Global Outcomes (KDIGO) 2012 Clinical Practice Guideline for the Evaluation and Management of Chronic Kidney Disease (CKD) in laboratory practice in Czechia and Slovakia. Materials and methods: An electronic questionnaire on adherence to KDIGO 2012 guideline was designed by an external quality assessment (EQA) provider SEKK spol. s.r.o. The questionnaire was placed and distributed through website to all medical biochemistry laboratories in Czechia and Slovakia (N = 396). Results: A total of 212 out of 396 laboratories responded to the questions, though some laboratories only answered some questions, those applicable to their practice. A total of 48 out of 212 laboratories adopted the KDIGO 2012 guideline in full extent. The metrological traceability of creatinine measurement to standard reference material of SRM 967 was declared by 180 out of 210 laboratories (two of the responding laboratories did not measure creatinine). Thirty laboratories are not well educated on traceability of creatinine measurement and seven laboratories do not calculate estimated glomerular filtration rate (eGFR). Both urinary albumin concentration and albumin to creatinine ratio are reported by 144 out of 175 laboratories (37 of the responding laboratories did not measure urinary albumin). Conclusion: Majority of laboratories in Czechia and Slovakia adopted some parts of the KDIGO 2012 guideline in their practice, but only 23% of the laboratories apply them completely. Thus, further education and action should be conducted to improve its implementation.
Keywords: Slovakia; směrnice jako téma; Slovenská republika; hodnoty glomerulární filtrace; kreatinin; průzkumy a dotazníky; Česká republika; laboratoře nemocniční; Renal Insufficiency, Chronic; lidé; Guidelines as Topic; chronická renální insuficience; Glomerular Filtration Rate; Humans; Creatinine; Surveys and Questionnaires; Laboratories, Hospital; Czech Republic